The effect of heating and cooling sintering rate on CaCu3Ti4O12 (CCTO) formation - Munirah Mohamad Zain (2017)
CCTO is the dielectric material that possessed giant dielectric constant. The purpose of this study is to investigate the effect of heating and cooling sintering rate on CCTO phase formation, density, microstructures and dielectric properties. The samples were prepared via solid state technique. The raw materials of CaCO3, CuO and TiO2 based on the calculated stoichiometric ratios were mixed for 24 hours. The powder mixture was calcined at 900 °C for 12 hours. The calcined powder were pressed into pellets and sintered at 1040 °C for 10 hours. Density and porosity were measured using Archimedes Principles, X-Ray Diffraction (XRD) was used to identify phase formation and Scanning Electron Microscope (SEM) was used to observed microstructure of the sintered pellets. The specimens showed the grain size decrease as heating rate increase. Microstructure displayed dense grain formation and hence yielded a high density for SP5. Formation of single phase of CCTO was found in all the sintered pellets. SP3 was identified to have larger and coarser grain when exposed to 3 °C/min of heating rate. In this study, SP5 was found as the optimum pellet that shown a good potential as dielectric material regarding the density and size of microstructure obtained.